Contemporary variant of a traditional Macedonian bondruck house - Dimkov, Gjorgji (National Library of Serbia, 2020)
The traditional bondruck system for constructing single-family homes, which is one of the most important segments of Macedonian material culture and heritage, can create a path for developing and improving contemporary design and construction solutions for sustainable architecture in Macedonia. The classic variant of traditional bondruck has not been of a high enough standard over a long period of use, which was also the case even at the time when it was a popular building method. Some disadvantages of its classic variants such as: the lack of quality materials for external and internal processing, inconsistent stability due to technological defects in the wood, a low standard and level of physical performance, functional deficiencies etc., can be overcome with modern technological solutions, the use of new building materials, and the possibility of systematic planning in a market economy, combined with the realization that a higher standard of housing is needed today. Based on an analysis of traditional Macedonian bondruck, it is possible to make a contemporary version of this system with improved quality of performance, both of individual elements and of the whole system. This is demonstrated by the proposed solution of a reference house in the village of Bitushe, built with the traditional bondruck system.
Keywords: contemporary, variant, traditional, Macedonian, bondruck house